The Evolution of Adolescent's Friendship Networks with Body Mass Index - Wu, Chyi-In (2017 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM), 2017)
The goal of the present study is to analyze the evolution of friendship network and body mass index (BMI) for adolescents in 3 different types of class---boy only, girl only, and boy and girl mixed. Complicated network surveys were administrated in classrooms on several high schools in Southern Taiwan. The participants are the students who attend these three types of class. Sociometric data were collected by having each student nominate up to 16 intimate classmates. Panel data was collected 7 times across 2 school semesters from Sep. 2008 to Jun. 2009. The program for dynamic social network analysis, SIENA, was applied to estimate the models for the evolution of adolescent's friendship networks and BMI. The result showed that BMI has effect on girls' class, but not boys'. In brief, the different composition of gender in a class will construct social norm about BMI and exerts different effect on network evolution. It is helpful for intervention plan focused on norms. Keywords: Friendship networks, BMI, Adolescent, Evolution of network